2011
DOI: 10.1063/1.3650706
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced coupled domain wall motions in a two-nanowire system

Abstract: In two closely spaced nanowires system, where domain walls exist in both of the nanowires, applying spin-polarized current to any of the nanowire will induce domain wall motions in the adjacent nanowire. The zero-current domain wall motion is accommodated by magnetostatic interaction between the domain walls. As the current density is increased, chirality flipping is observed in the adjacent nanowire where no current is applied. When current is applied to both nanowires, the coupled domain wall undergoes oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…4(b), before the distance between TWs reaches the final equilibrium value, the two TWs undergoe an oscillatory motion which is similar to the motion of coupled walls in two-nanostripe system. 27,28 Fig. 4(c) shows the x-axis component M x and y-axis component M y of the local magnetization (on y = 24nm) in the final metastable state as a function of x.…”
Section: Formation Of Multiple 360 O Structurementioning
confidence: 99%
“…4(b), before the distance between TWs reaches the final equilibrium value, the two TWs undergoe an oscillatory motion which is similar to the motion of coupled walls in two-nanostripe system. 27,28 Fig. 4(c) shows the x-axis component M x and y-axis component M y of the local magnetization (on y = 24nm) in the final metastable state as a function of x.…”
Section: Formation Of Multiple 360 O Structurementioning
confidence: 99%
“…We found that the interaction between two neighboring DWs that have the opposite magnetic charges is oscillatory in nature. 12,13 It is also possible to make use of the interaction to remotely drive a DW with a fixed chirality in the neighboring nanowire, without the direct application of current. 7 We showed that the remote drive technique can be extended by making use of the internal DW compression force to drive multiple DWs in the current-free nanowire.…”
mentioning
confidence: 99%
“…1(b)] is one of the simplest manifestations of coupled DWs. Despite great interest in this particular coupling both experimentally and numerically [4,5,10], no experimental observation of the coupled mode has yet been observed.…”
mentioning
confidence: 99%
“…These interactions can modify existing resonant behavior [1,2], lead to the appearance of new coupled modes [3][4][5], or result in a combination of these [6][7][8]. The coupling of DWs has also been proposed as a scheme towards increasing the output power of spin-torque oscillators [9], and will have an impact on the design of DW-logic-based devices as well.…”
mentioning
confidence: 99%